Consuming ideals: an archaeological investigation of the Social Hygiene Movement in Colorado - Griffin, Kristy Kay, author; Van Buren, Mary, advisor; Kwiatkowski, Lynn, committee member; Payne, Sarah, committee member (Colorado State University. Libraries, 2015)
Historical investigations of the Social Hygiene Movement (1890s-1930s) tend to focus on the urban origins of the concerns that sparked much of the resulting reform efforts. Furthermore, archaeological investigations that address artifacts associated with the Social Hygiene Movement often focus on either an urban or a rural setting, and usually only examine a single aspect of the movement rather than considering the impact of the totality of the movement’s ideology on American consumer behaviors. As a result, little is known about the materialization of the Social Hygiene Movement in the archaeological record and the differential appearance of associated artifacts at urban relative to rural sites. This project seeks to define Social Hygiene Movement-associated artifact types and undertake a comparative analysis of the occurrence of these artifacts at two urban and four rural sites in the state of Colorado in an effort to better understand the early material expressions of the movement in rural regions of the United States. This study was designed to 1) explore the assumption that artifacts related to health, hygiene, and cleanliness should appear at rural sites later than at urban sites, 2) determine if the Social Hygiene Movement manifested differently in rural regions relative to urban areas as evidenced in the archaeological record by types of consumer products purchased, and 3) if differences do exist, provide information about what other contextual and ideological factors may have caused the divergence. This project concludes that rural residents were likely aware of the emerging health, hygiene, and cleanliness ideals from nearly the beginning of the Social Hygiene Movement. However, differences in the frequency and types of products purchased suggest that consumer choices were informed by a shared system of rural values developed in opposition to the hegemonic rhetoric of Progressive Era reformers. The evidence presented in this study indicates that rural residents did not alter their hygienic practices and consumer behaviors to be in-line with urban standards, but rather selected the ideological aspects of the SHM that reinforced their rural identities and incorporated the products and practices which complemented their daily realities and social norms. The results highlight the importance of utilizing material studies in conjunction with historical research to achieve more nuanced understandings of the origins of the Social Hygiene Movement and question commonly-held assumptions based on the dominant discourse often evidenced in documentary sources.
Keywords: historical archaeology; rural identity; Colorado archaeology; Social Hygiene Movement; Progressive Era